Cooperativeness and impatience in the tragedy of the commons - Ernst Fehr; Andreas Leibbrandt (Institute for the Study of Labor (IZA), 2008)
This paper examines the role of other-regarding and time preferences for cooperation in the field. We study the preferences of fishermen whose main, and often only, source of income stems from using a common pool resource (CPR). The exploitation of a CPR involves a negative interpersonal and inter-temporal externality because individuals who exploit the CPR reduce the current and the future yield for both others and themselves. Accordingly, economic theory predicts that more cooperative and more patient individuals should be less likely to exploit the CPR. Our data supports this prediction because fishermen who exhibit a higher propensity for cooperation in a laboratory public goods experiment, and those who show more patience in a laboratory time preference experiment, exploit the fishing grounds less in their daily lives. Moreover, because the laboratory public goods game exhibits no inter-temporal spillovers, measured time preferences should not predict cooperative behavior in the laboratory. This prediction is also borne out by our data. Thus, laboratory preference measures are useful to capture important dimensions of field behavior.
urn:nbn:de:101:1-2008082097
Keywords: B4; 330; Cooperation; common pool resource; experiments; generalizability; methodology; Allmenderessource; Nichtkooperatives Spiel; Fischereiberufe; Kooperation; Test; Feldforschung